Comparison of mass spectrometry and flow cytometry in measuring minimal residual disease in multiple myeloma. (8th September 2021) - Foureau, David; Bhutani, Manisha; Guo, Fei; Rigby, Katherine; Leonidas, Marina; Tjaden, Elise; Fox, Andee; Atrash, Shebli; Paul, Barry; Voorhees, Peter M.; Usmani, Saad Z.
Abstract :